ANALYSIS OF QUANTUM SECURE DIRECT COMMUNICATION PROTOCOLS (Computer systems and information technologies, 2023)
The development of modern computer technologies endangers the confidentiality of information, which is usually ensured by traditional cryptographic means. This circumstance forces us to look for new methods of protection. In view of modern trends, quantum cryptography methods can become such alternatives, which allow solving a number of important cryptographic problems, for which the impossibility of solving using only classical (that is, non-quantum) communication has been proven. Quantum cryptography is a branch of quantum informatics that studies methods of protecting information by using quantum carriers. The possibility of such protection is ensured by the fundamental laws of quantum mechanics. One of the promising directions of quantum cryptography is Quantum Secure Direct Communication (QSDC) that offers secure communication without any shared key. A characteristic feature of this method is the absence of cryptographic transformations, accordingly, there is no key distribution problem. The purpose of this work is a general overview of quantum cryptography protocols, finding their weak points for further development and improvement, as well as identifying vulnerabilities to different attacks.The article analyzes new methods and protocols, as well as presents their advantages and disadvantages. Based on partial generalizations of theoretical provisions and practical achievements in the field of quantum cryptography, a generalized classification was developed. By comparing various factors of the protocols, and their resistance to certain cyberattacks, we have the opportunity to identify several problems in this field and expand the possibilities for choosing appropriate methods for building modern quantum information protection systems. In accordance with this, conclusions were presented regarding the use of protocols and increasing the level of their effectiveness.
Keywords: quantum cryptography; classification; quantum direct secure communication; quantum key distribution